Developing Financial Sources: The Case Of Small And Medium Enterprises In Vietnam - Xuan, Le Thanh; Trọng, Trịnh Đức; Phong, Le Thai (Advances in Social Sciences Research Journal, 2021)
Although Vietnam’s business environment has undergone fundamental changes to create favourable conditions for small and medium-sized enterprises (SMEs) to develop, SMEs are having difficulties in their existing operation and are facing constraints in accessing financial sources. This research aims to analyze the situation of financial sources and produce the relevant recommendations for small and medium enterprises in Vietnam. The authors use secondary data from government official websites of the Socialist Republic of Vietnam about Vietnam’s SME survey of Ha Noi Capital in the period 2014 – 2020. By observing and analyzing the collected data, the study provides a detailed description of the findings and relevant recommendations. After examining and investigating data and current studies about Vietnamese SMEs, the authors find that, in general, main constraints in accessing financial sources of SMEs are chiefly caused by (i) macroeconomic conditions, (ii) capacity management, (iii) lack of network and (iv) collateral requirements. The findings suggest implications for Vietnamese SMEs to improve financial sources should focus on: (i) training SMEs’ leaders to tackle potential risks and crises; (ii) creating new financial products and services in environmental and social development in Ha Noi Capital; (iii) developing new credit accessibility products without collaterals for SMEs. Different from prior studies that either provide current situation and list constraints of SMEs or make suggestions without sticking to the actual situation, the authors deliver a more comprehensive analysis about SMEs in the context of a developing country like Vietnam.